Thermo-mechanical coupling strategies in elastic–plastic problems - Vaz M.* (2017)
© 2016, Springer-Verlag Berlin Heidelberg.Modeling strategies aimed at thermo-mechanical coupled problems has been developed for a wide range of engineering applications. Staggered-type coupling procedures have been largely used in materials processing operations, especially in commercial codes, owing to their simplicity and flexibility. The present work shows that, in thermo-plastic problems, the classical implementation of the most common coupling procedure may present accuracy issues and time-stepping dependency. Numerical experiments indicate that an iterative coupling scheme constitutes a viable and simple approach to this class of problems.